Forage-Based Heifer Development Program for North Florida - Jose C.B. Dubeux; Nicolas DiLorenzo; Kalyn Waters; Jane C. Griffin (EDIS)
Florida has 915,000 beef cows and 125,000 replacement heifers (USDA, 2016). Developing these heifers so that they can become productive females in the cow herd is a tremendous investment in a cow/calf operation, an investment that takes several years to make a return. The good news is that there are options to develop heifers on forage-based programs with the possibility of reducing costs while simultaneously meeting performance targets required by the beef industry. Mild winters in Florida allows utilization of cool-season forages that can significantly enhance the performance of grazing heifers. During the warm-season, integration of forage legumes into grazing systems will provide additional nutrients to meet the performance required to develop a replacement heifer to become pregnant and enter the mature cow herd. In this document, we will propose a model for replacement heifer development, based on forage research performed in trials at the NFREC Marianna.